RyR-mediated Ca2+ release elicited by neuronal activity induces nuclear Ca2+ signals, CREB phosphorylation, and Npas4/RyR2 expression - Lobos, Pedro; Córdova, Alex; Vega-Vásquez, Ignacio; Ramirez, Omar; Adasme, Tatiana; Toledo, Jorge; Cerda, Mauricio; Härtel, Steffen; Paula-Lima, Andrea; Hidalgo, Cecilia (Proceedings of the National Academy of Sciences of the United States of America, 2021)
The expression of several hippocampal genes implicated in learning and memory processes requires that Ca2+ signals generated in dendritic spines, dendrites, or the soma in response to neuronal stimulation reach the nucleus. The diffusion of Ca2+ in the cytoplasm is highly restricted, so neurons must use other mechanisms to propagate Ca2+ signals to the nucleus. Here, we present evidence showing that Ca2+ release mediated by the ryanodine receptor (RyR) channel type-2 isoform (RyR2) contributes to the generation of nuclear Ca2+ signals induced by gabazine (GBZ) addition, glutamate uncaging in the dendrites, or high-frequency field stimulation of primary hippocampal neurons. Additionally, GBZ treatment significantly increased cyclic adenosine monophosphate response element binding protein (CREB) phosphorylation—a key event in synaptic plasticity and hippocampal memory—and enhanced the expression of Neuronal Per Arnt Sim domain protein 4 (Npas4) and RyR2, two central regulators of these processes. Suppression of RyR-mediated Ca2+ release with ryanodine significantly reduced the increase in CREB phosphorylation and the enhanced Npas4 and RyR2 expression induced by GBZ. We propose that RyR-mediated Ca2+ release induced by neuronal activity, through its contribution to the sequential generation of nuclear Ca2+ signals, CREB phosphorylation, Npas4, and RyR2 up-regulation, plays a central role in hippocampal synaptic plasticity and memory processes.